Cooperativas de crédito X bancos : análise da melhor opção para o cliente investidor ou captador de recurso - Caliman, Lorena (2017)
The brazilian banking market allows the offer of credit and investments by different financial institutions. In this market, similar products and services, with rates and competitive services charges, are offered by companies with different profiles, among them credit cooperatives, people's companies, and banks, capital companies. This study evaluated the best option for the investor or borrower, between operating with banks or with credit unions. A total of 728 records of banks and cooperatives were analyzed, comprising 16 financial institutions, distributed between December 2010 and December 2016. The work was developed based on two hypotheses, both comparing banks in relation to credit cooperatives. The first one states that banks offer the best option for the investor, considering the valuation of the shares, interest, dividends and services charges paid. The second hypothesis assures that banks offer the best option for the borrower, considering the rates practiced in credit operations. The results obtained allowed to accept the first hypothesis, since the final value in the investments made is on average 41% lower in cooperatives than in banks. The second hypothesis was rejected since the rate practiced in the credit portfolio of the cooperatives is on average 15% lower when compared to the bank rate. Lastly, the survey suggests that banks present the best option for current account holders, and credit unions are the best option for borrowers.